2000
DOI: 10.1002/1096-9896(200007)191:3<323::aid-path629>3.3.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Sites of prion protein accumulation in scrapie‐infected mouse spleen revealed by immuno‐electron microscopy

Abstract: Prion protein (PrP) from the brains of animals with transmissible spongiform encephalopathies is partially protease resistant (PrP res ) compared with fully sensitive PrP (PrP sen ) from uninfected brains. In most experimental models, PrP res is a reliable indicator of infectivity. Light microscopic studies have suggested that both PrP sen and disease-speci®c accumulations of PrP are associated with follicular dendritic cells (FDCs). Using immunogold electron microscopy, this study has demonstrated disease-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
77
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(85 citation statements)
references
References 23 publications
5
77
0
3
Order By: Relevance
“…Within the lymphoid tissues of patients with vCJD (24), most sheep with natural scrapie (56), or after experimental peripheral inoculation of rodents with scrapie (6,28,37,39,44), early PrP Sc accumulation takes place in the germinal centre on follicular dendritic cells (FDCs). Studies of mouse scrapie models have shown that mature FDCs are critical for replication in lymphoid tissues and, in their absence, neuroinvasion after peripheral challenge is significantly impaired (6, 17, 31, 37-39, 46, 51).…”
mentioning
confidence: 99%
“…Within the lymphoid tissues of patients with vCJD (24), most sheep with natural scrapie (56), or after experimental peripheral inoculation of rodents with scrapie (6,28,37,39,44), early PrP Sc accumulation takes place in the germinal centre on follicular dendritic cells (FDCs). Studies of mouse scrapie models have shown that mature FDCs are critical for replication in lymphoid tissues and, in their absence, neuroinvasion after peripheral challenge is significantly impaired (6, 17, 31, 37-39, 46, 51).…”
mentioning
confidence: 99%
“…Macrophages containing PrP Sc have been detected in ovine Peyer's patches, 46 other secondary lymph nodes of variant CJD patients, 47 and the spleen of mice. 48 In the spleen, PrP-positive cells were entirely CD14-positive macrophages (Figure 8). Jeffrey et al 48 revealed that such macrophages contained PrP Sc within lysosomes.…”
Section: Discussionmentioning
confidence: 97%
“…48 In the spleen, PrP-positive cells were entirely CD14-positive macrophages (Figure 8). Jeffrey et al 48 revealed that such macrophages contained PrP Sc within lysosomes. Additionally, the depletion of spleen macrophages by administrating clodronate to mice shows that macrophages partly control scrapie infection in peripheral tissues by sequestration of the scrapie inoculum and impairment of the replication of scrapie infectious agents in the spleen during the early stages of the disease.…”
Section: Discussionmentioning
confidence: 98%
“…Ainsi, le long de l'artériole centrale et de ses branches, on trouve des fibres sécrétant le neuropeptide-Y et des fibres à Met-enképhaline (peptide opioïde dérivé du clivage d'un précurseur, la pro-enképhaline A). Dans la pulpe blanche et la pulpe rouge on peut observer des fibres à cholécystokinine-8 3 . Enfin, le long de fins vaisseaux dans la pulpe blanche on trouve des fibres à neurotensine 4 .…”
Section: Revuesunclassified
“…La détection de PrP Sc à la surface des cellules folliculaires dendritiques (FDC), qui sont les cellules résidentes des centres germinatifs (CG), laissait présager un rôle important de ces cellules dans la rétention du pathogène [36] (➜). En effet, il a été démontré qu'après une infection périphérique, les FDC matures accumulent la PrP Sc [2,3]. La maturation des FDC est un point crucial dans le phénomène de lymphoinvasion et elle requiert la présence de lymphocytes B, porteurs de lymphotoxine /.…”
unclassified